Skeletal maturation, dietary intake and IGF-1 in elite gymnasts aged 9-17 years - Song, J. K.; Yoo, S. H.; Choi, H. H.; Kim, H. B. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to assess difference of skeletal maturity, dietary intake and IGF-1 between male and female gymnasts aged 9-17 years. Findings: In accord with previous studies it was found that elite gymnasts exhibit a specific pattern of growth characterized by a marked delay in skeletal maturation. As we expected, male gymnasts had significantly higher mean energy, iron and zinc intakes than female gymnasts (p < 0.05). These data provide evidence that female gymnasts were aware of their daily body weight, took extreme care regarding low-caloric food products, were knowledgeable about the nutritional components of their daily diet. Although several studies have reported a marked decrease in serum IGF-1 relative to swimmers and members of a nonathletic control group, no detectable differences were found between the groups in the present study. Further studies are required to examine the long-term effects of gymnastics training on circulating growth factors.